Electrochemical Noise Measurement for Corrosion Applications 1996
DOI: 10.1520/stp37954s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electrochemical Noise for Type 410 Stainless Steel in Chloride Solutions

Abstract: The electrochemical noise resulting from the corrosion of Type 410 stainless steel under open circuit conditions in solutions of widely different corrosivity has been examined. Parameters derived from electrochemical noise measurements and conventional electrochemical measurements were correlated with one another and with post-test examination of the specimens. Both the noise resistance and the polarization resistance increased with decreases in solution corrosivity. In all of the solutions studied, the noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 10 publications
4
17
0
1
Order By: Relevance
“…3 showed the plotting of the evaluations of this ratio, R n , and the corrosion rate in ranking order of corrosion rate from the samples of steel-reinforced concrete immersed in the corrosive testmedium in the study. This figure generally showed that the sample with the higher-valued R n was attended with low corrosion rate, while the sample with the lower-valued R n exhibited high corrosion rate, which finds agreement with Kelly et al [38] where R n values tracked linear polarisation resistance. These forms of results engender suggestions of the existence of relationship between the experimental data of corrosion rate and the noise resistance.…”
Section: Correlation Fittings and Analysis Of Corrosion Rate And Noissupporting
confidence: 89%
See 1 more Smart Citation
“…3 showed the plotting of the evaluations of this ratio, R n , and the corrosion rate in ranking order of corrosion rate from the samples of steel-reinforced concrete immersed in the corrosive testmedium in the study. This figure generally showed that the sample with the higher-valued R n was attended with low corrosion rate, while the sample with the lower-valued R n exhibited high corrosion rate, which finds agreement with Kelly et al [38] where R n values tracked linear polarisation resistance. These forms of results engender suggestions of the existence of relationship between the experimental data of corrosion rate and the noise resistance.…”
Section: Correlation Fittings and Analysis Of Corrosion Rate And Noissupporting
confidence: 89%
“…Noise resistance (R n ) modelling Requisite estimations, from the descriptive statistics exhibiting better compatibility with the scatter of the HCP and the ECC test-data were used for the ratio of the standard deviations of the corrosion potential and corrosion current, the noise resistance (R n ) as [26][27]31,[38][39]:…”
Section: Statistical Analysis Of Measured Corrosion Test-datamentioning
confidence: 99%
“…As could be observed in Figure 3, studies have shown that the corrosion noise resistance is generally high-valued at low corrosion rate and low-valued at high corrosion rate due to the fact that the corrosion noise resistance tracks the linear polarization resistance [36,56,59,60]. This relationship of corrosion noise resistance with corrosion rate, and vice versa, had been employed for detailing correlation expressions between these corrosion variables in reported works [36,56,60].…”
Section: Corrosion Rate and Corrosion Noise Resistance For Correlatiomentioning
confidence: 99%
“…Measurements of dispersion from the descriptive statistics that exhibited better compatibility with the scatter of the corrosion-potential and the corrosion-current test-data were used for modeling the corrosion noise-resistance [56,58,59]. This noise-resistance was modeled as the ratio of standard deviation of corrosion-potential (CP) to the standard deviation of corrosion-current (CC), using the formula in Equation (7):…”
Section: Initiation Of Corrosion Test-data Analyses-statistical Distrmentioning
confidence: 99%
“…Así, los métodos estadísticos se centran, fundamentalmente, en el estudio de la evolución en el tiempo de la desviación estándar de las señales de densidad de corriente, G¡, y de potencial, G E . La resistencia de ruido, R n , definida como el cociente o E lo v se ha relacionado con la resistencia de polarización, R p , y se ha discutido su validez para evaluar la velocidad de corrosión (2)(3)(4)(5).…”
Section: Introductionunclassified